Risk factors associated with cognitive dysfunction in patients on peritoneal dialysis: COGNITIVE DYSFUNCTION - Novković Joldić, Mira; Knežević, Violeta; Knežević, Milica (PONS - medicinski časopis, 2025)
Introduction: Cognitive impairments represent a significant global issue, as they deteriorate patients’ quality of life, increase mortality and the number of hospitalizations, burden the healthcare system, and raise treatment costs. Aim of procedure: The aim of this research is to determine the prevalence of cognitive dysfunction in patients undergoing peritoneal dialysis. Material and Methods: A cross-sectional study was conducted in May 2024, at the University Clinical Center of Vojvodina, at the Clinic for <nephrology and clinical immunology. The study included 30 patients undergoing peritoneal dialysis. The Montreal Cognitive Assessment (MoCA) was used as the instrument for assessing cognitive dysfunction. The maximum score is 30, and a result of <25 was considered indicative of cognitive dysfunction. Results: Of the 30 patients, 55.2% were male. The most represented age category was ≥60 years, comprising 43.5%. Among comorbidities, hypertension was the most prevalent at 33.3%. Cognitive dysfunction was confirmed in 34% of the patients. A logistic regression model was applied to identify predictors of cognitive dysfunction, revealing that female patients and those over 60 years of age were at a higher risk for cognitive dysfunction. A positive correlation between the MMSE score and the total dialysis adequacy index Kt/V was also identified. Conclusion: Significant predictors of cognitive dysfunction in patients on peritoneal dialysis were female gender, age category (above 60 years), glucose levels, daily and weekly doses of vitamin D, and the dialysis adequacy index Kt/V. Key words: cognitive dysfunction, peritoneal dialysis, risk factors